A dynamic thermal response on thermal conductivity at different temperature and moisture levels of EPS insulation. (September 2019) - Khoukhi, Maatouk; Hassan, Ahmed; Al Saadi, Salah; Abdelbaqi, Shaimaa
Abstract: In this work, the dynamic thermal effect of thermal conductivity, K-value, is investigated at different operating temperatures and moisture levels of polystyrene expanded insulation material (EPS) by using computational modelling of heat transport. In building energy analysis and assessment, the heat transfer through the building envelope usually considers a constant single K-value and neglects the effect of the moisture content within the insulation. In reality, the building envelope is subjected to the combined thermal and moisture gradients. Therefore, an accurate analysis requires a simultaneous calculation of both sensible and latent effects. The purpose of this paper is to analyze the dynamic thermal effect on the K-value of EPS by using the conduction finite difference (CondFD). The results of this research show a slight difference in the thermal conductivity value of EPS insulation at different operating temperatures for different densities of the material. However, a greater difference is observed at higher moisture contents compared with the dry sample when the K-value of the insulation is temperature dependent.